Kompetensi Lintas Budaya Guru-Guru Ekspatriat di Kota Semarang - Thomas Budi Santoso; Rudi Elyadi; Maria de Rosary Happy Satriany (Universitas Katolik Soegijapranata, Semarang, 2018)
This study was adescriptive-phenomenological analysis thataimed to describe the profile and cross-cultural competence expatriate teachers in Semarang.The study was conducted in five schools those were intentionally chosen for the reason that those schools employed expatriate teachers since the beginning of the program. The study used a set of questionnaire and an interview guide. Respondents of the study were 23(twenty three) expatriate teachers those were selected through snowball technique during a short study. The study found that expatriate teachers working inthe five selected schools were the professional teachers. This finding was evidenced by theteacher's certificate obtained from their home country that has been endorsed by the education attaché at the Indonesian embassy in their country. In the context ofcross-cultural competence, the study found that cross-cultural competence of expatriate teachers was categorized intothe moderate category.